How Flow Experience and Self-Efficacy Define Students’ Online Learning Intentions: View From Task Technology Fit (Framework) - Huang, Hai; Wang, Yong (Frontiers in Psychology, 2022)
The ongoing pandemic has transformed communication modes globally. Especially in the case of higher education, where countermeasures against coronavirus disease 2019 (COVID-19) have affected students’ learning experience. This study emphasized the case of business simulation games, where critical factors were underlined to define learners’ intention to use an online learning environment through the lens of task technology fit (TTF) as a theoretical stance. This study considered the statistical analysis of 523 students who attended the business simulation module online at the tertiary level of education. Findings conclude that flow experience is the most critical factor to define learners’ perceived TTF in the case of an online learning experience. However, the learners’ self-efficacy is significant enough to map learners’ intentions to use an online environment for learning. The study discussed several theoretical and practical implications for learners’ educators and policymakers.